Success of Big Infectious Disease Reimbursement Policy in China - Kun-xi Nie; Chan Wang; Xin-wu Li (SAGE Publishing, 2020)
Big infectious diseases do harm to the whole society, and it is highly crucial to control them on time. The major purpose of this article is to theoretically demonstrate that the Chinese government's intervention in large-scale infectious diseases is successful and efficient. Two potential strategies were considered: strategy 1 was infectious disease without government intervention, and strategy 2 was infectious disease with government intervention. By evolution model, this article illustrates the efficiency of big infectious disease reimbursement policy in China. Without government reimbursement, this article finds that high expenditures accelerate the disease infection. The number of infected persons decreases under big infectious disease reimbursement policy in China. The higher the treatment costs, the more important the government intervention. Big infectious disease reimbursement policy in China can serve as an efficient example to cope with big infectious diseases.